Contagion effect of restatements through common directorships - CHEN, Chih-Ying (Institutional Knowledge at Singapore Management University, 2010)
We predict that when a restatement is disclosed, information on the lower monitoring quality of the directors at the restating firms (“tainted directors”) can transfer to other firms these directors also serve on (“contagion firms”), and that this information transfer causes investors to reassess the credibility of the contagion firms’ financial reporting. Consistent with our predictions, we find that restatements at the restating firms also induce negative stock price reactions at the contagion firms. The stock price reactions are more negative if the contagion firms have lower financial reporting quality or if the tainted directors serve on the audit committees of the contagion firms. Overall, our results are consistent with a contagion effect of restatements through common directorships.